Worker characteristics and wage differentials: Evidence from a gift-exchange experiment - Florian Englmaier; Sebastian Strasser; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2011)
There is ample empirical evidence indicating that a substantial fraction of the population exhibits social preferences. Recent work also shows that social preferences influence the effectiveness of incentives in labor relations. Hence when making contracting decisions, employers should take into account that workers are heterogenous with respect to both their productivity and their social preferences. This paper presents causal evidence that they do. In a real-effort experiment, we elicit measures of workers' productivity and trustworthiness and make this information available to potential employers. Our data show that employers pay significant wage premia for both traits. Firms make highest profits with trustworthy workers, in particular with highly productive and trustworthy workers. We also document differences in the strength of gift exchange across worker types. In particular, output and profit levels of trustworthy workers are less dispersed than those of not-trustworthy workers.
Keywords: C91; J41; D86; 330; information; skills; laboratory experiments; gift exchange games; optimal contracts